Enhanced surveillance for gonorrhoea in two diverse settings in Queensland in the 2000s: comparative epidemiology and selected management outcomes - Fagan, Patricia S; Downing, Sandra G; McCall, Bradley J; Carroll, Heidi J; Howard, Therese M; Palmer, Cheryl M (Communicable Diseases Intelligence, 2013)
Gonorrhoea is an important sexually transmitted notifiable condition. This paper describes findings from 2 gonorrhoea enhanced surveillance programs operating during the 2000s in Queensland: one in the remote Torres and Northern Peninsula Area (T&NPA); the other in an urban region. The overall response rate in the T&NPA (2006–2011) was 82% (723 of 879), and in Brisbane Southside and West Moreton (BSWM) (2003–2011), it was 62% (1,494 of 2,401 notifications). In the T&NPA, cases were young (80% <25 years), Indigenous (97%) and 44% were male. In the BSWM, cases were predominantly male (76%), non-Indigenous (92%) and 42% were aged less than 25 years. Co-infection with chlamydia was found in 54% of males and 60% of females in the Torres, and in 18% of males and 35% of females in the BSWM. In the BSWM 35% of the men without a syphilis test recorded had reported sexual contact with men; similarly 34% of the men without an HIV test recorded had reported sexual contact with men. Compliance with recommended treatment (ceftriaxone) was greater than 90% in all years except 2008 (84%) in the T&NPA. Treatment compliance increased significantly, from 40% in 2003 to 84.4% in 2011 (P<0.0001) in the BSWM cohort. The proportion of contacts with a documented treatment date increased significantly in the T&NPA from 56% in 2009 to 76% in 2011 (P= 0.019), after a system for follow-up with the clinician became routine. Gonorrhoea epidemiology and management challenges vary across Queensland populations. Enhanced surveillance allows public health authorities to monitor epidemiology and reminds clinicians to prioritise effective sexually transmitted infection treatment for their clients. Commun Dis Intell 2013;37(3):E253–E259.